Analisis Persediaan Bahan Baku Cokelat Menggunakan Simulasi Monte Carlo UMKM Wondis Cokelat - Yaning Tri Hapsari; Ayunda Damayanti (Universitas Muria Kudus, 2026)
Raw material inventory management plays a crucial role in ensuring production sustainability, particularly for micro, small, and medium enterprises (MSMEs) that operate under fluctuating demand conditions. Wondis Cokelat MSME experiences challenges in aligning cocoa raw material usage with procurement planning, which may result in excess inventory or stock shortages. This study aims to estimate cocoa raw material requirements using the Monte Carlo simulation method based on historical consumption data. The research process includes the development of probability distributions, cumulative distributions, determination of random number intervals, random number generation, and simulation of raw material demand. The simulation results indicate that the estimated cocoa demand falls within a range close to actual conditions, with a Mean Absolute Percentage Error (MAPE) value of 14%. These findings suggest that the Monte Carlo simulation model demonstrates good predictive accuracy and can support inventory planning decisions.